Ketepatan Penerapan Kompetensi Absolut terhadap Gugatan Perbuatan Melawan Hukum Penguasa Oleh Komisi Pemilihan Umum (Kajian Putusan Pengadilan Negeri Nomor : 757/Pdt.G/2022/Pn Jkt Pst) - Muhammad Arifadi Nugroho; Rizky Ramadhan Baried (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The General Election Commission (KPU) as the defendant in District Court Decision Number: 757/Pdt.G/2022/Pn Jkt Pst, questioned the absolute competence of the district court in adjudicating the decision because the lawsuit filed by the PRIMA party was due to unlawful acts committed by the KPU. In this paper, the researcher formulates the first problem formulation of how the accuracy of the Central Jakarta District Court in adjudicating Decision Number: 757/Pdt.G/2022/Pn. Jkt Pst based on the teachings of judicial competence and secondly how the form of Unlawful Acts of the Ruler committed by the KPU in Decision Number: 757/Pdt.G/2022/Pn. Jkt Pst according to applicable law. This research uses normative legal research methods which examine legislation, norms, laws, and related theories to determine the form of unlawful acts of the authorities and the competence of the court. The results of the study explain that the accuracy of the district court in adjudicating the lawsuit of unlawful acts of the ruler is not appropriate because in the doctrine of legal norms, the theory of Absolute Competence that has the right to adjudicate is the Administrative Court, not the District Court. The form of unlawful acts of the KPU ruler is the KPU's actions in managing the SIPOL web and not fully implementing the decision of BAWASLU to harm the PRIMA party.